Epigenetic control of planarian stem cell potency limits stem activity and accurately defines differentiation programs - Mihaylova, Yuliana (2015)
Planarian flatworms are gaining popularity in regenerative medicine research due to the fact that they have unparalleled regeneration capacity. Their tissue recovery abilities are dependent on a pool of adult stem cells (neoblasts). Studies in the recent years have shown that epigenetic mechanisms have an important role in neoblasts’ self-renewal and differentiation properties. This thesis focuses on the study of trithorax-related genes and their function in neoblast regulation. Despite the fact that mammalian trithorax-related genes Mll3 and Mll4 are among the most frequently mutated genes in cancer, trithorax-related genes are the least well-studies members of the trithorax gene group (TrxG) of histone modifiers. The current study traced the evolutionary history of trithorax-related genes and concluded that they have undergone a number of independent gene fission events across phyla. In planarians, there are three partial orthologue of the mammalian Mll3 and Mll4 genes – Smed-LPT (corresponding to the N-terminus of Mll3/4), Smed-trr-1 and Smed-trr-2 (both corresponding to the C-terminus of Mll3/4). The three planarian trithorax-related genes are expressed in stem cells and control neoblast differentiation down certain lineages (brain, gut, eyes, pharynx, epidermis). Down-regulation of Smed-LPT results in hyperproliferation of stem cells, leading to tumour-like outgrowth formation. It was shown that trithorax-related genes’ function in stem cell regulation correlates with histone modification changes, specifically alterations in H3K4me1, H3K4me3 and H3K27me3. Future studies will focus on examining this correlation further via Next-Generation sequencing techniques.